Mulheres mulas do tráfico: estudo sobre a lei 11.343/06 sob uma perspectiva de gênero. - Costa, Luisa Vanessa Carneiro da (2019)
The present research refers to research involving questions about gender, drugs and prison in order to perceive the conditions of women mules, from a re-reading of the history of drugs, the challenges of the gender, thinking about the place of the woman and the prison experience in the Women's Penal Colony of Buíque-PE, through an interview with women mules, and professionals of the management team. With the general aim of analyzing the situation of women trafficking mules in the Buíque-PE Women's Criminal Colony, in comparison to Law 11.343/ 06, which deals with drugs, and its policies, bodies and measures, establishing norms and defining crimes, ducts and other aspects of use, production or trafficking. As the main authors that served as theoretical contribution for this research were: Rodrigues (2006), Foucault (2009), Alvarenga (2016), Teles (2007) e Saffioti (2004). This work is an ethnographic study, with a qualitative approach. The types of research used were: bibliographic, descriptive and exploratory, starting from a non-participant observation, which made use of field diary, and semi-structured interview, being the information read in the light of content analysis. The conclusions of the present research are taken from analyzes of the thematic categories, in turn, it is verified that the interviewees suffer doubly with the reinforcements of gender and their penalties (legal and social), so that archaic notions still offer goals to a perspective of denying "being a woman" in prison and beyond, extending also to the members of the patriarchate family structure, so that the sanction serves as a reinforcement to previous disciplines. From this perspective, the following categories and sub-categories were listed: 1) Women mules in the prison: everyday meanings and practices of prison reality, as subcategories: Mule woman in prison system: comprising stories of lives before prison; The incarcerated woman: oppressive and subaltern practices; Women prisoners and jurisdictional provision: ruptures and misfortunes; Imprisoned women and barriers to access to health; Practices of sorority among women prisoners in the Women's Criminal Colony of Buíque-PE; Beyond the bars: confrontations of women after prison life. 2) Second category of analysis: Women mules: selectivity, drug trafficking and gender vulnerability. 3) Third thematic category: The female prison reality and interpersonal relations, which is divided into three subcategories: Relation of mules women to society: sexism and misogyny, Affective relations and family practices: experiences of female mules in prison, A double punishment of the incarcerated woman: prisoners to abandonment - intimate visits and the sexual issue in prison. As the fourth thematic category: 4) The Female Penal Colony of Buíque-PE under the perception of management and a fifth category: 5) Public policies of attention to women mules in prison. With this, we observe how the prison life of these women, invisible by society and the State, during the speeches of management professionals and their own perceptions, this dialogue between the narratives served as information that subsidized the results of this work, prisons, gender and drug policy issues. Also, it is noticed that the presence of the companion is not frequent in the life of these mules women, since the intimate visit does not happen frequently due to factors such as the disdain of the partner, for example, that impacts on the sexual rights of the interviewees, and that official institutions working in the prison context reinforce total violence practices in relation to the prison system and the judiciary. Thus, we observe, with the reports obtained in the interview, that these women fight for equality of gender, class and opportunities, so that they can see each other through the practice of sorority; evidencing, therefore, that the machismo is present intensively in the life of this public.